2008
DOI: 10.1177/089686080802803s34
|View full text |Cite
|
Sign up to set email alerts
|

Characteris Tics and Causes of Immune Dysfunction Related to Uremia and Dialysis

Abstract: From the immunologic viewpoint, chronic kidney disease (CKD) is characterized by disorders of both the innate and adaptive systems, generating a complex and still not fully understood immune dysfunction. Markers of a chronically activated immune system are closely linked to several complications of CKD and represent powerful predictors for mortality in the CKD population. On the other hand, CKD patients respond poorly to vaccination and to challenges such as bacterial infection. Interestingly, the main causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(49 citation statements)
references
References 34 publications
0
46
1
2
Order By: Relevance
“…That is, the functions of polymorphonuclear leukocytes, monocytes, macrophages, APCs, and lymphocytes in maintaining an efficient immune response are affected by multiple causes including increased oxidative stress and inflammation, priming of leukocytes, accumulation of uremic toxins, increased apoptosis of immune cells, disturbed renal metabolic effects, and dialysis-related factors (e.g., interactions between the blood and dialysis equipment, the presence of endotoxins in the water used for dialysis, access-related infections, and PD solutions with a high glucose concentration, low pH, or the presence of glucose degradation products represent chronic stimuli for the inflammatory response ( 2 3 4 5 6 7 8 9 10 ). These abnormalities of immune cells lead to an increased propensity to infection, a diminished response to vaccination, a decreased production of antibodies in response to specific stimuli by B cells, and an impaired cell-mediated immunity ( 8 9 10 ). Furthermore, it has been reported that dysfunctions of the immune system are associated with a high prevalence of cardiovascular disease and mortality in patients with ESRD ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the functions of polymorphonuclear leukocytes, monocytes, macrophages, APCs, and lymphocytes in maintaining an efficient immune response are affected by multiple causes including increased oxidative stress and inflammation, priming of leukocytes, accumulation of uremic toxins, increased apoptosis of immune cells, disturbed renal metabolic effects, and dialysis-related factors (e.g., interactions between the blood and dialysis equipment, the presence of endotoxins in the water used for dialysis, access-related infections, and PD solutions with a high glucose concentration, low pH, or the presence of glucose degradation products represent chronic stimuli for the inflammatory response ( 2 3 4 5 6 7 8 9 10 ). These abnormalities of immune cells lead to an increased propensity to infection, a diminished response to vaccination, a decreased production of antibodies in response to specific stimuli by B cells, and an impaired cell-mediated immunity ( 8 9 10 ). Furthermore, it has been reported that dysfunctions of the immune system are associated with a high prevalence of cardiovascular disease and mortality in patients with ESRD ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aberrant PTH/Ca/P levels have been linked to infection in dialysis patients beyond the scope of CKD-MBD and vascular calcification related cardiovascular morbidity and mortality 19 , 25 . The underlying mechanism may be associated with systemic immune dysregulation 26 , 27 . In fact, in vitro experimental data have indicated that immune cell functions could be modulated by different concentrations of PTH, Ca or P, although these functional alterations in uremic patients may not be consistent with in vitro data due to their complex interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Uremia-related immune dysfunction is a complex interaction between the innate and adaptive systems, in which persistent immune activation and immune suppression coexist [ 15 ]. The pathogenic mechanisms of these immunological abnormalities have been ascribed in part to uremic toxins, malnutrition, iron overload, dialysis-related factors, and possibly apoptosis [ 16 – 19 ].…”
Section: Discussionmentioning
confidence: 99%